THEORETICAL APPROACHES TO DETERMINING THE MONITORING OF LAND USE OF OBJECTS OF THE NATURE RESERVE FUND: Array - Viatkin, R.; Viatkin, K. (Municipal economy of cities. Series: «Economy science», 2020)
The purpose of the article is to study theoretical approaches to determining the monitoring of the use of objects of the nature reserve Fund. The paper analyzes the existing theoretical approaches to determining the monitoring of land objects of the nature reserve Fund, which showed their fragmentation and lack of common provisions. As a result of systematization of theoretical approaches to the justification of monitoring the use of land objects of the natural reserve Fund of the regions, the author proposed its definition, which is characterized by a set of legal, constructive, complex, organizational, functional and instrumental directions.At the present stage, there are a number of problematic aspects of determining the monitoring of objects of the nature reserve Fund, namely: - the need for a monitoring system should be linked to the regulatory framework for the use of nature reserve facilities and with national institutions at different levels of management;- the need to strengthen the mechanisms for financing the objects of the nature reserve Fund;- formation and improvement of existing systems for monitoring objects of the nature reserve FO-NDU;- the need to apply a comprehensive monitoring of objects of the nature reserve Fund by creating information support and methods for its assessment. The result of the proposed approach is the development of a system for monitoring land use of objects of the nature reserve Fund of Ukraine, which takes into account a set of information-analytical and spatial data on the state of objects of the nature reserve Fund using modern methods of data analysis and processing, visualization tools and automated systems for studying the state and dynamics of changes in the eco-network. It should be noted that the existing scientific developments in the system of monitoring the use of land objects of the natural reserve Fund of the regions do not take into account the instrumental aspects of its development and implementation. They are based on a comprehensive application of modern tools, in particular, geodesic, geoinformation systems, space survey results, and modern specialized software.